Rib fixation: Who, What, When?. Issue 1 (27th April 2017) - de Moya, Marc; Nirula, Ram; Biffl, Walter
Abstract : Rib fractures are among the most common traumatic injury found in ∼20% of all patients who suffer thoracic trauma. The majority of these are a result of a blunt mechanism and are often associated with other traumatic injuries. The most common associated injury is lung contusion. Rib fractures impart an increased morbidity and mortality with the highest mortality associated with a flail chest in the elderly population. Flail chest is defined radiographically as 3 or more consecutive ribs fractured in 2 or more places. This often translates to a clinical flail which is associated with paradoxical chest wall movement during respiratory cycles. The mainstay of treatment has been pain control and respiratory support with positive pressure ventilation. However, over the past 2 decades, there has been mounting evidence to suggest that open reduction and internal fixation of ribs benefits patients. The indications remain confined to the most severely injured patients with flail chest or chronic non-unions; however, there remains debate whether or not less severely injured patients would benefit as well. This article will review the current evidence and provide proposed indications based on available evidence and current expert opinion.